2011
DOI: 10.1155/2011/729598
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Plasticity and β2‐Adrenergic Receptors: Adaptive Responses of β2‐Adrenergic Receptor Expression to Muscle Hypertrophy and Atrophy

Abstract: We discuss the functional roles of β2-adrenergic receptors in skeletal muscle hypertrophy and atrophy as well as the adaptive responses of β2-adrenergic receptor expression to anabolic and catabolic conditions. β2-Adrenergic receptor stimulation using anabolic drugs increases muscle mass by promoting muscle protein synthesis and/or attenuating protein degradation. These effects are prevented by the downregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
46
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 86 publications
(152 reference statements)
2
46
0
1
Order By: Relevance
“…Numerous studies have shown that β2-agonists induce muscle hypertrophy in many species [10][11][12][13][14][15][16][17][18][19][20][21][22] . Experiments in mice lacking β1-AR, β2-AR, or both subtypes, have demonstrated that clenbuterol-induced effects, such as muscle hypertrophy, are mediated by β2-AR 10) .…”
Section: Anabolic and Metabolic Adaptations To β2-agonists And Exercisementioning
confidence: 99%
See 4 more Smart Citations
“…Numerous studies have shown that β2-agonists induce muscle hypertrophy in many species [10][11][12][13][14][15][16][17][18][19][20][21][22] . Experiments in mice lacking β1-AR, β2-AR, or both subtypes, have demonstrated that clenbuterol-induced effects, such as muscle hypertrophy, are mediated by β2-AR 10) .…”
Section: Anabolic and Metabolic Adaptations To β2-agonists And Exercisementioning
confidence: 99%
“…Experiments in mice lacking β1-AR, β2-AR, or both subtypes, have demonstrated that clenbuterol-induced effects, such as muscle hypertrophy, are mediated by β2-AR 10) . β2-agonists promote muscle growth by stimulating protein synthesis and reducing protein degradation [11][12][13] . Furthermore, the hypertrophic response to β2-agonists is known to appear more frequently in fast-twitch muscles [11][12][13][14][15][16][17][18][19][20][21][22] .…”
Section: Anabolic and Metabolic Adaptations To β2-agonists And Exercisementioning
confidence: 99%
See 3 more Smart Citations